Review: LC coupled to low- and high-resolution mass spectrometry for new psychoactive substance screening in biological matrices : where do we stand today? - Meyer, Markus Robert; Maurer, Hans H. (Analytica chimica acta, 2016)
The field of new psychoactive substances (NPS) is highly dynamic and the situation changes from year to year. Therefore, the current review provides a timely update about the latest developments to help analysts keep the pace with NPS distribution. It covers PubMed-listed studies published between January 2014 and January 2016 dealing with the application of liquid chromatography (LC) coupled low- and high-resolution mass spectrometry (MS) for broad screenings for NPS in clinical (CT) and forensic (FT) toxicology. Latest developments and applications are highlighted and selected papers critically discussed. Comprehensive tables summarizing all discussed articles complete the overview. Finally, an outlook on the future of LC coupled MS in CT and FT is provided and readers will learn why low-resolution mass spectrometry might remain the standard for the next couple of years at least for easy-to-use quantitative screening procedures.
Gesehen am 14.01.2019